Microbial and Small Eukaryotes Associated With Reefs in the Upper Gulf of Thailand - Bulan, Dewi Embong; Wilantho, Alisa; Tongsima, Sissades; Viyakarn, Voranop; Chavanich, Suchana; Somboonna, Naraporn (Frontiers in Marine Science, 2018)
Reef sites of Ko Samae San (S), Khao Ma Cho (K) and Ko Tao Mo (T) in the upper Gulf of Thailand have abundant corals and represent a hotspot of marine biodiversity. Coral reefs serve as major networks of food and energy, where bacteria, microbial eukaryotes (fungi) and small eukaryotes play significant roles as primary producers that convert inorganic compounds to organic compounds, degraders of toxic substances, and recyclers. These functions sustain food and energy supplies. Advances in metagenomics and next-generation sequencing can provide knowledge of diversity without cultivation limitations (e.g. culture media and culture condition). Scientists have researched bacterial diversity of coral sites; however, a database for fungi and small eukaryotes from Thailand’s sites with abundant corals is lacking. The present study utilized metagenomics combined F-RISA and 18S rRNA gene sequencing to unveil the first culture-independent microbial and small eukaryotes from these sites at two times in year and across four species of corals (Porites lutea, Platygyra sinensis, Acropora humilis and Acropora millepora), seawater and sediment. Results showed that the small eukaryotic communities on corals were distinct from communities in the surrounding seawater and sediment. The communities were relatively similar at the three sites and during the two periods of time. Pearson’s correlations indicated the community diversity were associated with water quality (e.g. dissolved oxygen concentrations and density of water).